Using temperament and character dimensions (TCI) to analyze the personality profiles of adults and older adults with cancer managed in outpatient settings - Vespa, Anna; Giulietti, Maria Velia; Fabbietti, Paolo; Di Rosa, Mirko; Gattafoni, Pisana; Berardi, Rossana; Arnaldi, Giorgio; Balercia, Giancarlo; Spatuzzi, Roberta (Frontiers in Psychology, 2024)
Introduction This study aimed to investigate profiles of personality evaluated by temperament and character dimensions (TCI) in 638 adult and older adult patients (CP) who had recently been diagnosed with breast, colon, lung, and other kinds of cancer (female and male subjects were assessed). Tests: Temperament and Character Inventory (TCI). Statistical analysis: cluster K-means analysis for personality traits. Results Two different personality profiles emerged: “Low self-determination and pessimism” (Profile 1) and “Self-determination and self-caring (medium)” (Profile 2). The following significant differences were observed in the TCI dimensions between the two profiles: Temperament-Novelty-Seeking (NS) (p < 0.001); Harm-Avoidance (HA) (p < 0.001); Reward-Dependence (RD) (p < 0.001); Persistence (PS) (p < 0.001); Character-Self-Directness (SD) (p < 0.001); Cooperativeness (C) (p > 0.001); Self-Transcendence (ST) (p < 0.001). No differences in the two profiles were found between adult and elderly patients. Profile 1 - “Low self-determination and pessimism”: Patients with this profile present low resistance to frustration, poor search for novelty and solutions (NS), anxiety and pessimism (medium HA), high social attachment and dependence on the approval of others (medium-high RD), and low self-determination (PS) as temperament dimensions; and medium-low self-direction, low autonomy and ability to adapt (SD-medium-low), medium cooperativeness (C), and low self-transcendence (ST) as character dimensions. Profile 2 - “Self-determination and self-caring (medium)”: Patients with this profile have resistance to frustration, ability to search for novelty and solutions (medium-NS), low anxiety and pessimism (HA), low social attachment and dependence on approval (medium-low-RD), and determination (medium-high PS) as dimensions of temperament; and autonomy and capacity for adaptation and self-direction (SD), capacity for cooperation (high-CO), and self-transcendence (medium-high-ST) as character dimensions. Conclusion Personality screening allows a better understanding of the difficulties of the individual patient and the planning of targeted psychotherapeutic interventions that promote quality of life and good adaptation to the disease course.